GELIAT EKONOMI KREATIF PASCA COVID-19: PERAN PEMERINTAH DALAM MENGEMBANGKAN IKM MALL DI KOTA CIREBON - Kusuma, Nurul Rahmah; Ayuni; Wijaya , M. Robby; Syahidaniyah, Marwa; Jumali, Jujun; Qurrotu’ain, Nella; Sari , Putri Nurlela (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
National economic growth is largely determined by the dynamics of the regional economy, while the regional economy is generally supported by small and medium-scale economic activities, as well as the creative economy. restore and develop SMEs. This study aims to analyze the government's role in developing post-covid-19 MSMEs in Cirebon City. This research method uses a qualitative approach that originates from primary and secondary data sources through structured interview techniques, literature, and documents related to the research object. The results of the study show that the Cirebon city government under the Office of Cooperatives and Small and Medium Enterprises has played an effective role as a facilitator, educationist, and catalyst for developing MSMEs in Cirebon City post-covid-19 by creating a new label for Small and Medium Industries (IKM) to become IKM Mall ( Serving You Through Services) to market MSME products, carry out empowerment, in the form of training, develop online and offline digi corners, e-catalog programs for MSME products that have not been displayed in galleries, and assist marketing by placing advertisements on billboards using the name of the IKM Mall and digital promotion through social media, as well as making innovations such as creating an MSME database in the form of an application. Kata kunci: IKM Mall, MSME, Creative Economy, Role of Government, Post Covid-19